Unprecedented Climate Change in India and a Three-Pronged Method for Reliable Weather and Climate Prediction - Brahmananda Rao, Vadlamudi; Ashok, Karumuri; Govardhan, Dandu (Frontiers in Climate, 2021)
India, one of the most disaster-prone countries in the world, has suffered severe economic losses as well as life losses as per the World Focus report1. Over 80% of its land and more than 50 million of its people are affected by weather disasters. Disaster mitigation necessitates reliable future predictions, which need a focused climate change research. From the climate change perspective, the summer monsoon, the main lifeline of India, is predicted to change very adversely. The duration of the rainy season is going to shrink and pre-monsoon drying can also occur. These future changes can impact the increase of vector-borne diseases such as malaria, dengue, and others. In another recent study, 29 world experts from various institutions found that the largest exposure to disasters like tropical cyclones, river floods, droughts, heatwaves, is over India. improved, and skillful prediction, we suggest a three-staged cumulative method, namely, K is for observational analysis, U is for knowledge & understanding, and M is for modelling & prediction. In this brief note, we report our perspective of imminent weather disasters to India namely, monsoons and tropical cyclones, and how the weather and climate forecasting can be improved, leading to a better climate change adaptation.